Impact of Credit Risk Management on Profitability of Commercial Banks in Nepal - Kalwar, Arjun K; Shrestha, Binay (Journal of Economics and Management, 2024)
The research aims to assess commercial bank credit risk and profitability, analyze the link between credit risk and financial performance of sampled banks, and assess the influence of credit risk on financial performance. Descriptive, correlational, causal comparative study. Secondary data come from the sample bank. Three Nepalese commercial banks are sampled. Profitability, credit risk, liquidity, capital sufficiency, interest spread, and base rate are study factors. Financial and statistical analysis are based on objective achievement and raw facts. Financial analysis uses ratios and descriptive statistics, correlation, and regression. Using SPSS and Excel for analysis. Positive but not significant relationships exist between profitability, credit risk, and liquidity. The capital adequacy ratio and profitability are negative and insignificant. Profitability is positively correlated with interest spread. Base rate negatively impacts profitability and is considerable. Credit risk hurts profitability but not much. The liquidity ratio and capital sufficiency positively affect profitability but not significantly. Positive interest spread and negative base rate affect bank profitability. With a R square value of 0.783, the study found that independent factors explain 78.3% of the variation in the dependent variable and other variables 21.7%. The results indicated that ISR and BR significantly affect commercial bank ROE in Nepal, but CR, LR, and CAR do not.